Field notes of the Hare Indians, 1961 - Hara, Hiroko, 1934- (1961)
This item consists of 4 field notebooks (109 pages) of Hiroko Sue Hara. The notebooks contain primarily linguistic notes, principally also a 43-page vocabulary, organized by ethnographic categories such as animals, fish, clothing, tools, etc.; 36 pages of phrases and vocabulary notes; and a slip file. This material is related to Recording 38, reels 1-6. Originals in possession of Hiroko Sue Hara.